2015
DOI: 10.1080/15592324.2015.1087629
|View full text |Cite
|
Sign up to set email alerts
|

Promoters ofAaGL2andAaMIXTA-Like1genes ofArtemisia annuadirect reporter gene expression in glandular and non-glandular trichomes

Abstract: Herein, we report cloning and analysis of promoters of GLABRA2 (AaGL2) homolog and a MIXTA-Like (AaMIXTA-Like1) gene from Artemisia annua. The upstream regulatory regions of AaGL2 and AaMIXTA-Like1 showed the presence of several crucial cis-acting elements. Arabidopsis and A. annua seedlings were transiently transfected with the promoter-GUS constructs using a robust agro-infiltration method. Both AaGL2 and AaMIXTA-Like1 promoters showed GUS expression preferentially in Arabidopsis single-celled trichomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Even in Artemisia annua promoters of AaGL2 and AaMIXTA LIKE drive the expression of reporter gene in non-glandular trichomes of Arabidopsis, as well as in both glandular and T shaped trichomes of Artemisia annua (Sunita Jindal et al 2015). Since the expression of ATGL2 is controlled by WRKY transcription factor TTG2 by binding to W box (TGACT) found in the promoter of ATGL2 (Ishida et al 2007), and the presence of W box has been reported in the promoter of AaGL2) Jindal et al 2015). In addition to this overexpression of WD 40 repeat from Artemisia annua rescued the trichomeless phenotype of ttg1 mutant in Arabidopsis (Wang et al 2016).…”
Section: Conservation Among Regulators Of Trichome Development In Plantsmentioning
confidence: 86%
“…Even in Artemisia annua promoters of AaGL2 and AaMIXTA LIKE drive the expression of reporter gene in non-glandular trichomes of Arabidopsis, as well as in both glandular and T shaped trichomes of Artemisia annua (Sunita Jindal et al 2015). Since the expression of ATGL2 is controlled by WRKY transcription factor TTG2 by binding to W box (TGACT) found in the promoter of ATGL2 (Ishida et al 2007), and the presence of W box has been reported in the promoter of AaGL2) Jindal et al 2015). In addition to this overexpression of WD 40 repeat from Artemisia annua rescued the trichomeless phenotype of ttg1 mutant in Arabidopsis (Wang et al 2016).…”
Section: Conservation Among Regulators Of Trichome Development In Plantsmentioning
confidence: 86%
“…One way involves the genetic ablation of GSTs in peripheral organs. Several promoters upstream of trichome genes in tobacco, tomato, cotton, and Artemisia annua have been shown to induce reporter gene expression in GSTs 38 42 ; thus, these promoters could be used for the genetic ablation of GSTs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jindal et al . () cloned a MIXTA homolog, AaMIXTA‐like1, from A. annua and used a transient assay to show that its promoter was able to direct expression of a reporter in both GST and TSTs, but no functional analysis of the gene was undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest that the molecular mechanism for formation of multicellular trichomes in A. annua may be very distinct from the one involved in formation of unicellular trichomes in Arabidopsis. Interestingly, Jindal et al (2015) cloned a MIXTA homolog, AaMIXTA-like1, from A. annua and used a transient assay to show that its promoter was able to direct expression of a reporter in both GST and TSTs, but no functional analysis of the gene was undertaken.…”
Section: Researchmentioning
confidence: 99%